Process mining analysis to enhance systematic workflow of an IT company. (19th June 2023) - Porouhan, Parham
This study explores the application of Fluxicon Disco, a process mining tool, on an event log collected from an IT company. The analysis conducted using Fluxicon Disco provides insights into the following issues: identification of slow and time-consuming activities, abnormal activity behaviours, loops, repeated and redundant activities, abnormal clusters/variants, cases handled inefficiently, specific paths and relationships, congestions and bottlenecked areas, time intervals/gaps for cases with 'high priority', in addition to relationships and connections between task groups. The results of the analysis indicate that the software can identify inefficiencies and areas for improvement in the company's processes, providing valuable insights for process optimisation. The study concludes that the application of process mining tools such as Fluxicon Disco can significantly contribute to the identification and resolution of process-related issues in organisations. Eventually, the paper provides useful insights for researchers and practitioners interested in analysing business processes, process discovery and process optimisation.